2018
DOI: 10.3390/nu10101536
|View full text |Cite
|
Sign up to set email alerts
|

Key Findings and Implications of a Recent Systematic Review of the Potential Adverse Effects of Caffeine Consumption in Healthy Adults, Pregnant Women, Adolescents, and Children

Abstract: In 2016–2017, we conducted and published a systematic review on caffeine safety that set out to determine whether conclusions that were presented in the heavily cited Health Canada assessment, remain supported by more recent data. To that end, we reviewed data from 380 studies published between June 2001 and June 2015, which were identified from an initial batch of over 5000 articles through a stringent search and evaluation process. In the current paper, we use plain language to summarize our process and find… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…9 Through its Caffeine Working Group and affiliated industry organisations, including the American Beverage Association and the National Coffee Association, ILSI has supported the production of a body of published articles depicting caffeine as a benign substance posing little or no threat to fetal health and development. [114][115][116][117][118][119][120][121] Scientific evidence to the contrary has been portrayed in that literature as methodologically flawed due to confounding from uncontrolled variables.…”
Section: Are Caffeine-related Negative Pregnancy Outcomes Merely Unexmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Through its Caffeine Working Group and affiliated industry organisations, including the American Beverage Association and the National Coffee Association, ILSI has supported the production of a body of published articles depicting caffeine as a benign substance posing little or no threat to fetal health and development. [114][115][116][117][118][119][120][121] Scientific evidence to the contrary has been portrayed in that literature as methodologically flawed due to confounding from uncontrolled variables.…”
Section: Are Caffeine-related Negative Pregnancy Outcomes Merely Unexmentioning
confidence: 99%
“…Spurious conclusions have been a recurring feature of industry-affiliated commentary. [114][115][116][117][118][119][120][121] For example, one review concluded that the "evidence does not support a positive relationship between caffeine consumption and adverse reproductive or perinatal outcomes" (p. 2573, emphasis added), 117 while another concluded that daily consumption of caffeine is "not associated with adverse reproductive and developmental effects" (p. 637, emphasis added). 119 Yet, in reality, even industry-affiliated commentaries agree with independent opinion that maternal caffeine consumption is associated with (ie, has a 'positive relationship' with) negative pregnancy outcomes.…”
Section: Are Caffeine-related Negative Pregnancy Outcomes Merely Unexmentioning
confidence: 99%
See 1 more Smart Citation
“…It has various benefits such as respiratory stimulation in premature infants with sleep apnea [1] [2]. World Journal of Cardiovascular Diseases However, it is most frequently consumed in beverages or as over-the-counter capsules, pills and tablets to boost one's energy [3]- [8]. Thus, abuse of caffeine has become a habit for many people even though there are unanswered questions about its effects on the body, especially the brain and cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…some clinical benefits such as respiratory stimulation in premature infants suffering from sleep apnea [1] [2]. However, it is most commonly consumed in beverages and as over-the-counter capsules, pills and tablets because consumers believe it boosts their energy, enhances motivation, improves gym performance, and/or reduces disease [3]- [8]. Thus, abuse of bodies and minds by caffeine has become a pastime for many consumers even though there are unanswered questions about its aphysiological effects on the body, especially the brain and cardiovascular system.…”
mentioning
confidence: 99%